R.E.S.P.E.C.T.: Transforming Bullies of Lecheria National High School through Behavior Modification - Sanchez, Evelyn (JPAIR Institutional Research, 2019)
Bullying in school is an issue around the globe that creates a negative impact on the whole educational system. Researchers have conducted studies worldwide, but mostly focusing on the effects that it has on the bullied. In this research, the focus was on the impact that it has on the bully and be able to craft a behavior modification program that would address the bullying behavior of the students. This study aimed to determine the effect of the profile of bullies, namely reasons, types, and objects of bullying, and that of the school climate on the bullies’ behavior. To gather data, the researcher made use of the Swearer Bully Survey System to measure bullying behavior and the Authoritative School Climate Survey by Dewey Cornell to measure the school climate. Respondents of the research were sixty students from Grade 7 to 10 of Lecheria National High School. Results revealed that bullying has a significant impact on the behavior of the bullies. On the other hand, school climate does not have a substantial impact on the bullies’ behavior. After a thorough investigation, the researcher has crafted a behavior modification program R.E.S.P.E.C.T. (Reflective and Empathetic Series of Program to Elevate Character Transformation) to lessen, if not eradicate, the increasing number of bullying cases in school.
Keywords: Social Science; bullying behavior; causal design; Calamba City; Laguna; Philippines